STAGES OF THE DEVELOPMENT OF THE ANALYSIS OF ECONOMIC ACTIVITY IN THE EDUCATION SYSTEM - Власюк, Тетяна Миколаївна (Journal of Strategic Economic Research, 2023)
The article studies the development of economic analysis in the system of education. The main stages of the development of economic analysis and higher education are determined on the basis of logical and comparative analysis, a chronology of the development of the analysis of economic activity in the education system is built on the basis of deductive and inductive methods. It was determined that in the medieval period (10th–15th centuries) economic analysis was aimed only at recording the facts of economic life, which mainly related to commodity exchange transactions; in the Renaissance (16th–17th centuries) and the Enlightenment (17th – the beginning of the 19th centuries) quantitative assessment of the economic life of educational establishments and qualitative evaluation of registered information were carried out; in the industrial era (the end of the 19th – beginning of the 20th centuries), the analysis of balance sheets of some educational institutions and accounting analysis were conducted; the post-industrial era (the second half of the 20th century) was marked by the formation of analysis as a separate function of management, two analytical approaches were developed – external analysis (of the system of education) and internal analysis (of an educational institution). In the era of economic transformation and digitalization to the levels Industry 4.0 and Sociaty 5.0 (the beginning of the 21st century), economic analysis in education continuoues its development, studies on the analysis of the development of the world market of higher education, on the development of national and regional markets of educational services, and on the analysis of economic activity of some educational institutions appear. It is substantiated that currently the analysis of economic activity in the education system should be aimed at identifying the strengths and weaknesses of regulatory and legal support, resource potential (material and technical, educational and methodical, informational), students contingent formation, personnel support, scientific potential, international activity, economic activity and its financial results.